2022
DOI: 10.18006/2022.10(5).1115.1120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein levels of commercial diets on the growth performance and survival rate of rabbitfish (Siganus guttatus) at the nursing stage

Abstract: This study aimed to determine the effect of a commercial diet's protein level on the fry-to-fingerling stage. Thirty days-old fries having the initial length and weight of 18.25 ± 0.15 mm fish-1 and 0.036 ± 0.50 g fish-1 respectively have been used in this study. Diet having three protein levels i.e. 30% (trial 1 as control), 35% (trial 2), 40% (trial 3), and 45% (trial 4), respectively, have been used to evaluate the effect of protein, and each trial has been repeated three times. During the study, stocking d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Mass production of fry is still constrained by high mortality rates and severe larval metamorphosis (Juario et al, 1985). They can be caused by broodstock nutrition, environmental conditions during broodstock rearing, and nutrition during the larval stage (Ayson, 1989;Tran et al, 2023;Kieu at el., 2023;Nguyen et al, 2015;Phuong et al, 2022). Reports in Siganus guttatus showed that the addition of iodide to the feed was related to changes in thyroid hormones, thyroxine (T4), and triiodothyronine (T3) during early larval development.…”
Section: Introductionmentioning
confidence: 99%
“…Mass production of fry is still constrained by high mortality rates and severe larval metamorphosis (Juario et al, 1985). They can be caused by broodstock nutrition, environmental conditions during broodstock rearing, and nutrition during the larval stage (Ayson, 1989;Tran et al, 2023;Kieu at el., 2023;Nguyen et al, 2015;Phuong et al, 2022). Reports in Siganus guttatus showed that the addition of iodide to the feed was related to changes in thyroid hormones, thyroxine (T4), and triiodothyronine (T3) during early larval development.…”
Section: Introductionmentioning
confidence: 99%